A cell-permeable peptide inhibitor of p55PIK signaling alleviates ocular inflammation in mouse models of uveitis. (October 2020) - Zhu, Meijuan; Yang, Hongxia; Chen, Zhen; Xia, Xianmin; Deng, Qinqin; Shen, Yin
Abstract: Purpose: Previously we developed TAT-N24 as a synthetic cell-permeable peptide inhibitor of p55PIK signaling and demonstrated its anti-inflammatory effects. This study aimed to evaluate the potential of TAT-N24 as a new agent for the treatment of ocular inflammatory diseases. Methods: The endotoxin-induced uveitis (EIU) model was established by intravitreal injection of lipopolysaccharide (LPS) in BALB/c mice and experimental autoimmune uveitis (EAU) model was established by subcutaneous injection of a peptide spanning amino acid residues 161–180 of interphotoreceptor retinoid binding protein (IRBP161-180) with complete Freund's adjuvant (CFA) in B10.RIII mice. TAT-N24 was topically administered in EIU model and intraperitoneally administered in EAU model. The severity levels of uveitis were assessed by clinical and histopathological scores. The mRNA levels of inflammatory cytokines in iris-ciliary body (ICB) and retina were analyzed by reverse transcription quantitative polymerase chain reaction (RT-qPCR). The protein levels of inflammatory factors were determined by ELISA or Western blotting. Results: The results showed that TAT-N24 alleviated clinical signs, decreased inflammatory cell infiltration and the expression of inflammatory cytokines in both EIU and EAU models. Furthermore, protein levels of tumor necrosis factor-alpha (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) in aqueous humor and mRNA and protein levels of NF-κB p65 in the ICB significantly decreased in EIU model. In EAU model, TAT-N24 application induced a significant decrease of IFN-gamma (IFN-γ) and interleukin-17 (IL-17) in the retina, which were secreted by Th1 and Th17 cells, respectively. Conclusion: In conclusion, TAT-N24 suppressed intraocular inflammation in both EIU and EAU models, and the anti-inflammatory effects were mediated by suppressing the expression of inflammatory cytokines by PI3K/NF-κB signaling pathway. TAT-N24 could be potential candidate for the treatment of ocular inflammatory diseases. Highlights: TAT-N24 is a synthetic cell-permeable peptide inhibitor of p55PIK signaling. Topical administration of TAT-N24 alleviated acute ocular inflammation in EIU model. Intraperitoneal injection of TAT-N24 alleviated chronic ocular inflammation in EAU model. TAT-N24 alleviated ocular inflammation by suppressing the production of inflammatory cytokines. Anti-inflammatory effects of TAT-N24 were mediated by inhibiting NF-κB activation.